Uncovering The Effectiveness of the Project-Based Learning Model and Ecological Intelligence: Impact on Environmental Problem-Solving Ability in Senior High School - Nurul Safia Rianti; Sugeng Utaya; Purwanto Purwanto; Rajendra P Shrestha (Universitas Negeri Gorontalo, 2024)
Equipping students with proficient environmental problem-solving skills is critical in the 21st century to address pressing global problems. This research explores the effectiveness of Project-Based Learning (PjBL) combined with ecological intelligence as a strategy to increase students' cognitive understanding and environmental awareness. A quasi-experimental design with a pre-test and post-test control group design was used. The participants were class XI IPS (Class XI IPS) students from SMA Negeri 1 Karangrejo (n = 5 classes). Purposive sampling resulted in an experimental class that was exposed to PjBL and a control class that followed traditional learning. Data collection was carried out through descriptive tests and observations that were validated and reliable. Two-way ANOVA analysis showed a significant positive effect (p less than 0.05) between PjBL and ecological intelligence on students' environmental problem solving abilities. Interestingly, no significant interaction effects (p greater than 0.05) were detected, indicating the potential dominance of the PjBL structured learning environment. These findings highlight the potential of PjBL as a pedagogical tool to foster environmental literacy and problem solving in geography education